Effect of baseline CD4 cell count at linkage to HIV care and at initiation of antiretroviral therapy on mortality in HIV-positive adult patients in Rwanda: a nationwide cohort study. Issue 9 (September 2015) - Nsanzimana, Sabin; Remera, Eric; Kanters, Steve; Forrest, Jamie I; Ford, Nathan; Condo, Jeanine; Binagwaho, Agnes; Bucher, Heiner; Thorlund, Kristian; Vitoria, Marco; Mills, Edward J
Summary: Background: Continued debate exists about whether initiation of antiretroviral therapy (ART) in symptom-free patients at higher baseline CD4 cell counts results in important clinical benefits. We aimed to examine to what extent baseline CD4 cell count at linkage to HIV care and at ART initiation predicts mortality in adults with HIV in Rwanda. Methods: We included data for patients with HIV in Rwanda who were aged 15 years or older and linked to care or initiated ART between Jan 1, 1997, and April 30, 2014, from nationally representative databases. We analysed the effect on mortality of baseline CD4 cell count at ART initiation and at linkage to care. Follow-up time was measured from time of ART initiation and from linkage to HIV care to study exit. To account for effect modification by time, we stratified by era of linkage (before 2008 vs 2008 or after) and for other indications for initiation of ART. We also stratified CD4 cell count by indication to initiate ART other than CD4 cell count status. We used Cox proportional hazard regressions to examine the effect of CD4 cell count at linkage and at ART initiation on mortality. Findings: Our analysis was based on data from 50 147 patients who initiated ART and 72 061 patients linked to care. In the late era (2008 and after), linkage to care at a CD4 cell count of 100–199 cells per μL without any further indication was associated with higher mortality than linkage at 200–349 cells per μL (hazard ratio [HR] 1·37, 95% CI 0·95–1·97); the effect was much the same for initiation of ART in this CD4 stratum (1·37, 0·92–2·04). For higher CD4 strata, linkage to care at 500 cells per μL or more was protective (0·53, 0·39–0·72), whereas the reported effect of initiation of ART on mortality was not distinguishable from chance alone (0·82, 0·21–3·20). Interpretation: Efforts are needed to link and retain patients early in pre-ART HIV care. In settings where ART is not yet available for immediate treatment, retention in a strong pre-ART programme is effective at improving survival. Funding: TheBill & Melinda Gates Foundation .